Prevalence of diabetes mellitus and hypertension in people living with human immunodeficiency virus on antiretroviral therapy in Gweru district, Zimbabwe - Laston Gonah; Indres Moodley; Khumbulani Hlongwana (AOSIS, 2020)
Background: While antiretroviral therapy (ART) has markedly increased survival in people living with human immunodeficiency virus (PLHIV), emerging trends of co-existence of non-communicable diseases (NCDs) and HIV could negate the gains already achieved in controlling HIV. Aim: The study aimed to determine the prevalence of hypertension and diabetes mellitus in PLHIV on ART in Gweru district. Setting: Six high-volume ART sites in Gweru district under Midlands province in Zimbabwe. Methods: This was a cross-sectional study. Screening and data collection occurred over a 3-month cycle when all patients were expected to have visited the ART sites for their monthly ART drug supply. The process also allowed the identification of health system challenges regarding data management for HIV-NCD comorbidity. Poisson regression analysis was used to calculate NCD prevalence ratio (PR) in PLHIV. Results: Nearly 18 000 PLHIV registered for ART were identified. Hypertension (19.5%) and diabetes mellitus (8.4%) were the most common NCDs identified with a high proportion of those who did not know their diagnosis (over 50%). The prevalence of hypertension and/or diabetes mellitus among women was 74.9% compared to 25.1% in men (PR 3.22; 95% CI: 3.07-5.51, p = 0.0000). Other factors associated with increased prevalence of hypertension and/or diabetes mellitus were age group of ≥ 60 years (PR 2.5; 95% CI: 1.42-3.22, p = 0.00023), and duration of ≥ 5 years on ART (PR 6.4; 95% CI: 4.70-8.01, p = 0.0011). Separate data collection for NCDs and HIV was a key challenge affecting quantification of magnitude of HIV-NCDs comorbidity and subsequently management of NCDs in PLHIV. Conclusions: Indications of increasing prevalence of NCDs in PLHIV call for integrated electronic data management for HIV, TB and NCDs. This will allow active NCD case finding, and eventually improve prevalence data and treatment for HIV-NCD comorbidity. Future studies should focus on the health experiences and access to treatment in PLHIV diagnosed with NCDs; and to establish the accurate manner in which HIV status, ART and NCDs might be associated, through conducting a case control or cohort study.